REACTIVE POWER COMPENSATION AND STABILIZATION OF THE OUTPUT VOLTAGE OF THE TRACTION SUBSTATIONS - Kolb, O. O. (Science and Transport Progress, 2006)
A vectorial principle of voltage inverter control has been offered on the basis of the unified spatial current/voltage vectors in the revolving system of coordinates for compensation of reactive power and stabilizing the voltage.